Christian Natural Law and a Foundation for Religious Freedom: Love, the True, and the Good - Alex Deagon (Australian Journal of Law & Religion)
This article is a summary version of my book Christian Natural Law and Religious Freedom: A Foundation Based on Love, the True and the Good (Routledge, forthcoming 2026). It aims to begin a conversation with respect to articulating a theological foundation for religious freedom. For this purpose, I consider natural law in the Christian tradition. In Part I, I briefly survey the diversity of Christian natural law and argue that Radical Orthodoxy enables the identification of common themes across the breadth of Christian natural law. These themes include the Good (a set of basic goods and the common good), the True (divine revelation as specially revealed in Scripture and generally revealed in nature), and Love (the law of love as ultimately displayed through Christ). In Part II, I draw on these themes of Good, True, and Love to sketch a theological framework for religious freedom. Fundamentally, religious freedom is an expression of the Good because it allows people to pursue the good of religion, which contributes to a flourishing community; it is an expression of the True because it aims towards receiving the revelation of God; it is an expression of Love because it brings people to the ultimate Good and Truth — God Himself — which is only possible through the loving sacrifice of Christ on the cross.